2011
DOI: 10.1016/j.ijnurstu.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Action research studies in the intensive care setting: A systematic review

Abstract: Based on this review it appears that action research is a promising methodological approach to address clinical practice improvement in the ICU. Studies retrieved focussed primarily on process and formative evaluation but not on clinical outcomes. There is a need to incorporate outcome assessment in action research in the ICU to increase the framework of action research to improve clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 37 publications
4
50
1
Order By: Relevance
“…This pattern reflects the comments made in Chapter 2 from the systematic reviews by Soh et al 87 and by Munn-Giddings et al…”
Section: Participatory and Action Researchsupporting
confidence: 75%
See 1 more Smart Citation
“…This pattern reflects the comments made in Chapter 2 from the systematic reviews by Soh et al 87 and by Munn-Giddings et al…”
Section: Participatory and Action Researchsupporting
confidence: 75%
“…Several reviews have examined action research but have found that the impacts on patient care and health outcomes are often not covered. For example, Soh et al 87 reviewed action research studies in intensive care settings but of the 21 studies included only one described improved health-care outcomes. 88 Munn-Giddings et al 89 reviewed studies of action research in nursing published between 2000 and 2005.…”
Section: Action Research and Participatory Action Researchmentioning
confidence: 99%
“…In the first phase, the participatory dimension of the practice development probably contributed to satisfaction and was an incentive to reorganizing the traditional ICU to a dedicated ICU ward for CCI patients. It has been argued that such an approach empowers staff and therefore gives a greater feeling of autonomy [30], an important factor for ICU nurses' job satisfaction [20]. In the first phase, working with teams to increase their knowledge about the CCI and developing new knowledge was successful in developing practice and may have impacted team satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This collaborative relationship is an essential component of action research enabling sustainable change, both to patient care and the work environment [23], as shown in the Heart Beads program and emphasised in other programs utilising this approach [14, 15, 17, 19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…Action research allows knowledge development which can be applied back to the practice area from which it was created [19]. An advantage of an action research approach is the collaborative relationship between the researchers, staff, patients, and families in the clinical setting that can enable sustainable changes to patient care and the work environment [23]. …”
Section: Introductionmentioning
confidence: 99%